Wanita Teladan : Istri-Istri, Putri-Putri & Sahabat Wanita Rasulullah - Mahmud Mahdi Al-Istambuli, Mustafa Abu Nashr Asy-Syilby (Irsyad Baitus Salam, 2005)
Wanita Teladan : Istri-Istri, Putri-Putri & Sahabat Wanita Rasulullah